Seasonal small-scale spatial variability in alpine snowfall and snow accumulation - Scipión, Danny (2013)
In mountainous regions, snow accumulation on the ground is crucial for mountain hydrology and water resources. The present study investigates the link between the spatial variability in snowfall and in snow accumulation in the Swiss Alps. A mobile polarimetric X-band radar deployed in the area of Davos (Switzerland) collected valuable and continuous information on small-scale precipitation for the winter seasons of 2009/2010 and 2010/2011. Local measurements of snow accumulation were collected with airborne laser-scanning for the winters of 2007/2008 and 2008/2009. The spatial distribution of snow accumulation exhibits a strong interannual consistency that can be generalized over the winters in the area. This unique configuration makes the comparison of the variability in total snowfall amount estimated from radar and in snow accumulation possible over the diverse winter periods. As expected, the spatial variability, quantified by means of the variogram, is shown to be larger in snow accumulation than in snowfall. However, the variability of snowfall is also significant, especially over the mountain tops, leads to preferential deposition during snowfall and needs further investigation. The higher variability at the ground is mainly caused by snow transport.